2003
DOI: 10.1103/physrevlett.90.195001
|View full text |Cite
|
Sign up to set email alerts
|

Sheared Poloidal Flow Driven by Mode Conversion in Tokamak Plasmas

Abstract: A two-dimensional integral full-wave model is used to calculate poloidal forces driven by mode conversion in tokamak plasmas. In the presence of a poloidal magnetic field, mode conversion near the ion-ion hybrid resonance is dominated by a transition from the fast magnetosonic wave to the slow ion cyclotron wave. The poloidal field generates strong variations in the parallel wave spectrum that cause wave damping in a narrow layer near the mode conversion surface. The resulting poloidal forces in this layer dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 20 publications
1
72
0
Order By: Relevance
“…16 are improved by increasing the poloidal resolution to N m = 255 poloidal modes. Figure 4 shows how the higher resolution studies follow the scaling of the experimental data with 3 He concentration, while the lower resolution fails to capture the increased electron damping as the 3 He concentration increases and the separation of the ion-ion hybrid layer and the 3 He fundamental cyclotron layer increases. One possible cause of the overshoot in the higher resolution cases at large 3 He concentration is the decreasing single pass absorption caused by the larger evanescent region between the cyclotron layer and MC layer.…”
Section: Fig 1: Toric Simulation Of a D(mentioning
confidence: 99%
See 2 more Smart Citations
“…16 are improved by increasing the poloidal resolution to N m = 255 poloidal modes. Figure 4 shows how the higher resolution studies follow the scaling of the experimental data with 3 He concentration, while the lower resolution fails to capture the increased electron damping as the 3 He concentration increases and the separation of the ion-ion hybrid layer and the 3 He fundamental cyclotron layer increases. One possible cause of the overshoot in the higher resolution cases at large 3 He concentration is the decreasing single pass absorption caused by the larger evanescent region between the cyclotron layer and MC layer.…”
Section: Fig 1: Toric Simulation Of a D(mentioning
confidence: 99%
“…For a 3 He concentration of 24%, the MC layer and the 3 He fundamental layer are separated by approximately 7 cm. In Wright et al, 13 we have shown graphically in 13 twodimensional field plots how at low resolution, the excitation of the fields at the MC layer is not localized within the layer but follows the flux surface geometry around toward the the low field side to the 3 He resonance where it causes spurious 3 He power deposition.…”
Section: Convergence Study For D( 3 He) Mode Conversion In the Amentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an asymmetric toroidal mode profile results in a difference in the intensity and wavelength of the ICW propagating above and below the mid--plane. This is because both the toroidal and poloidal mode numbers contribute to the large k ∥ of the ICW, and the positive poloidal mode effectively increases k ∥ for the ICW below the mid--plane while the negative poloidal mode number decreases k ∥ for the ICW above the mid--plane due to the backward propagating nature of the wave [34]. We also notice that the ICW is damped strongly in the parallel direction by electron Landau damping, which could be useful for localized current drive in the tokamak [27--30].…”
Section: Applicationsmentioning
confidence: 99%
“…However, the driven flow in Alcator C-Mod and JET was in the opposite direction. This may partially be explained by direct rf torque input 11,12 , but the physics of net flow generation is still not well understood.…”
Section: Introductionmentioning
confidence: 99%